PENGARUH ATRIBUT PRODUK WISATA DAN ELECTRONIC WORD OF MOUTH (eWOM) TERHADAP KEPUTUSAN BERKUNJUNG PADA OBYEK WISATA UMBUL SIDOMUKTI KABUPATEN SEMARANG - Nurul Retno Hapsari; Nawazirul Lubis; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2014)
Tourism is one of the fastest growing industries today. Consequently, people think that travelling is a lifestyle nowadays. This phenomenon led to increase tourist numbers. It also experienced by Umbul Sidomukti, a holiday destination with REAL concepts in Mount Ungaran. But the tourist numbers continued to declined from 2009 to 2013.Tourist will looking information before making decisions. Electronic Word of Mouth (eWOM) has been one of the resources that are used frequently. Furthermore, tourist will assess how the tourism product attributes offered. Therefore, this paper aims to examine tourism product attributes and electronic word of mouth’s influence on travel decisions in Umbul Sidomukti. The type of research is explanatory research. Interviews with questionnaire were adopted for data collection in this study. Hundred people were employed as respondent by purposive sampling technique. They were Umbul Sidomukti’s tourist who reside in Semarang and find out about Umbul Sidomukti from internet.The research results showed that tourism product attributes and electronic word of mouth influenced on travel decisions, partially or simultaneously. The results obtained by analyzing primary data with validity test, reliability test, crosstab analysis, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, and a significance (t anf F) using SPSS for Windows version 15,0.Based on the results, the researcher suggests that Umbul Sidomukti’s management has to improve infrastructures such as roads and road signage, provision of public transportation, provide innovation on tourism products, and manage Umbul Sidomukti’s website to be more informative and interactive so the tourist numbers can increase.